2017
DOI: 10.1302/1863-2548-11-160266
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pelvic fracture pattern and overall orthopaedic injury burden in children sustaining pelvic fractures based on skeletal maturity

Abstract: Purpose The purpose of this study was to review pelvic fractures and concomitant orthopaedic injuries in children who have a patent triradiate cartilage (TRO) compared with children whose triradiate cartilage has closed (TRC). We hypothesise that these injuries will differ, leading to correlated alterations in management.Patients and Methods Using a database, we retrospectively reviewed patients aged below 18 years with pelvic fractures presenting to our Level 1 trauma center. Radiographs and CT scans were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(14 reference statements)
0
5
0
3
Order By: Relevance
“…The Advantages of TiRobot Over Traditional Surgical Techniques Biomechanical studies confirmed that the stability of the anterior and posterior pelvic rings accounted for 40% and 60% [27][28][29][30] . The stability of the posterior pelvic ring is maintained by the sacroiliac joint complex, which is composed of the bilateral ilium, the sacrum, the sacroiliac joint, and the surrounding ligaments; it also plays an important role in the stability of the pelvic ring 21 .…”
Section: Discussionmentioning
confidence: 98%
“…The Advantages of TiRobot Over Traditional Surgical Techniques Biomechanical studies confirmed that the stability of the anterior and posterior pelvic rings accounted for 40% and 60% [27][28][29][30] . The stability of the posterior pelvic ring is maintained by the sacroiliac joint complex, which is composed of the bilateral ilium, the sacrum, the sacroiliac joint, and the surrounding ligaments; it also plays an important role in the stability of the pelvic ring 21 .…”
Section: Discussionmentioning
confidence: 98%
“…This is supported by several studies, which found that children with an open triradiate cartilage (i.e. more immature) were also likelier to be hit by automobiles 38,40 . Children are also more likely to sustain a lateral compression pelvic injury in contrast to adults, who usually sustain an antero‐posterior compression injury 37 .…”
Section: Discussionmentioning
confidence: 63%
“…more immature) were also likelier to be hit by automobiles. 38,40 Children are also more likely to sustain a lateral compression pelvic injury in contrast to adults, who usually sustain an antero-posterior compression injury. 37 Crashes involving vehicle intrusion or older children (age > 12 years old) increased the likelihood of pelvic fractures.…”
Section: Mechanism Of Injurymentioning
confidence: 99%
“…Anatomically, the immature pediatric patient skeleton offers better flexibility with greater joint (sacroiliac and symphysis pubis) laxity and abundant cartilage, which allows for superior shock absorption and an increased remodeling potential [7,24]. These inherent characteristics of the paediatric patients' pelvis encouraged more nonsurgical lines for PPF management, including bed rest, traction, pelvic slings, or hip spica casts [12,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%